Dependence of element composition of bile of freshwater and marine fishes on some abiotic and biotic factors - Mikhail M. Solovyev; Anastasiya V. Shokurova; Olesya V. Anishchenko; Pavel G. Vlasenko; Elena N. Kashinskaya; Karl B. Andree (Frontiers in Marine Science, 2023)
Introduction The elemental composition and physical properties of fish bile is a very important marker for ecotoxicological and physiological studies as bile is able to accumulate elements from environmental compartments. In the present study we focused on the effects of long term (seasons and years) and spatial distance (different water bodies) as well as other biotic (feeding habits, fish species, gut morphology) and abiotic (water salinity) factors on element composition of bile of 429 individuals belonging to 22 forms/species of fishes. Methods Element composition was determined using an inductively coupled plasma optical emission spectrometry. The fishes were analyzed from one marine (the Kandalaksha Gulf of the White Sea), two freshwater oligotrophic (Teletskoye and Baunt lakes), and one freshwater eutrophic water body (Chany Lake). In parallel, we have estimated the volume and density of bile from the same fishes using an automatic pipette and electronic balance. Results and discussion Based on fish bile density and volume data, we hypothesize that gastric fish species (those fishes that have a stomach) require a low volume of bile, but with higher density if compared to agastric fish species (those lacking a stomach) that mainly possessed large volumes of bile, but with a lower density. We have found that the concentrations of the following Na, K, Ca, Mg, S, P (major elements) and Al, Cu, Fe, Sr, Zn (trace elements) were the highest among the 28 elements studied. There were significant findings to contribute to a better understanding of the physiology of bile. First, we have determined the conditions formed in a water body in a given year (season) are more important for element composition of fish bile rather than other tested factors (feeding habits, gut morphology, etc.). Second, the feeding habits of fishes (carnivorous compared to non-carnivorous) had a significant effect based on differences among several elements. Third, the clear distinction between marine and freshwater fishes was found only for K and Na. Understanding which elements are produced as part of waste elimination and those that are present as a consequence of vital biological functions could improve the ecotoxicological study of bile as a marker of heavy metal contamination.